The New Locality of Chenopodium Pumilio R. Br. in Poland - Witosławski, Piotr (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2009)
The clammy goosefoot Chenopodium pumilio R. Br. is a rare anthropophyte in the Polish flora. Hitherto, this species was recorded in Gdańsk and Rybnik. The present study describes the newly-discovered locality in Stryków near Łódź (Central Poland), the occurrence of this species in Poland and the general geographical distribution in the world.